TINJAUAN HUKUM TERHADAP PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) BERDASARKAN PERATURAN MANTERI AGRARIA DAN TATAT RUANG KEPALA BADAN PERTANAHANAN NASIONAL NO.6 TAHU 2018 DI BPN KABUPATEN KARO - Yuda Efrimsa; Maslon Hutabalian; Maria Ferba Editya S (Journal Recht (JR), 2022)
Legal Review of the Implementation of Complete Systematic Land Registration (PTSL), To find out the Legal Review of the Implementation of Complete Systematic Land Registration based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 6 of 2018 at the ATR/BPN Land Office of Karo Regency and to find out obstacles in Implementation of Complete Systematic Land Registration (PTSL) at the ATR/BPN Land Office of Karo Regency and Implementation of PTSL in Spatial Planning for the Community. The data collection technique used in this study was by means of a study of literature and analyzed qualitatively. The results of this study indicate that the implementation of PTSL has several activities that are combined with other activities or programs including cross-sectoral certificate programs, mass self-help certification programs, mass redistribution programs of landform objects, land consolidation, and transmigration and other mass certification programs or a combination of several program of activities stated in the law. Barriers to the implementation of complete systematic land registration (PTSL) are caused by technical and legal factors as well as the function of implementing PTSL in spatial planning for the community, including technical barriers, legal barriers, and community customary factors